\(\dfrac{7}{5}\) - \(\dfrac{1}{5}\) / x + 3 / = 1
Tìm x, biết:
a) \(\dfrac{-2}{5}\) + \(\dfrac{4}{5}\) . x = \(\dfrac{3}{5}\)
b) \(\dfrac{-3}{7}\) - \(\dfrac{4}{7}\) : x = \(\dfrac{2}{5}\)
c) \(\dfrac{4}{7}\) . x + \(\dfrac{2}{3}\) = \(\dfrac{-1}{5}\)
d) \(\dfrac{5}{7}\) : x -1 = \(\dfrac{2}{3}\)
a, - \(\dfrac{2}{5}\) + \(\dfrac{4}{5}\).\(x\) = \(\dfrac{3}{5}\)
\(\dfrac{4}{5}\).\(x\) = \(\dfrac{3}{5}\)+ \(\dfrac{2}{5}\)
\(\dfrac{4}{5}\).\(x\) = 1
\(x\) = \(\dfrac{5}{4}\)
b, - \(\dfrac{3}{7}\) - \(\dfrac{4}{7}\): \(x\) = \(\dfrac{2}{5}\)
\(\dfrac{4}{7}\): \(x\) = - \(\dfrac{3}{7}\) - \(\dfrac{2}{5}\)
\(\dfrac{4}{7}\): \(x\) = - \(\dfrac{29}{35}\)
\(x\) = \(\dfrac{4}{7}\): (- \(\dfrac{29}{35}\) )
\(x\) = - \(\dfrac{20}{29}\)
c, \(\dfrac{4}{7}\).\(x\) + \(\dfrac{2}{3}\) = - \(\dfrac{1}{5}\)
\(\dfrac{4}{7}\).\(x\) = -\(\dfrac{1}{5}\) - \(\dfrac{2}{3}\)
\(\dfrac{4}{7}\).\(x\) = - \(\dfrac{13}{15}\)
\(x\) = - \(\dfrac{13}{15}\): \(\dfrac{4}{7}\)
\(x\) = - \(\dfrac{91}{60}\)
d, \(\dfrac{5}{7}\): \(x\) - 1 = \(\dfrac{2}{3}\)
\(\dfrac{5}{7}\): \(x\) = \(\dfrac{2}{3}\)+ 1
\(\dfrac{5}{7}\): \(x\) = \(\dfrac{5}{3}\)
\(x\) = \(\dfrac{5}{7}\): \(\dfrac{5}{3}\)
\(x\) = \(\dfrac{3}{7}\)
Tìm x:
a) \(\dfrac{-3}{7}\).x=\(\dfrac{3}{56}\).\(\dfrac{28}{9}\)
b) x-\(\dfrac{3}{16}\)=\(\dfrac{7}{15}\):\(\dfrac{3}{5}\)
c) \(\dfrac{2}{5}\)+\(\dfrac{1}{5}\).x=\(\dfrac{5}{6}\)
d) \(\dfrac{3}{4}\)x-\(\dfrac{2}{5}\)x=\(\dfrac{3}{7}\).\(\dfrac{1}{6}\)+\(\dfrac{5}{7}\).\(\dfrac{1}{6}\)
*Lưu ý: Trình bày chi tiết kết quả.
a)\(x=\left(\dfrac{3}{56}\cdot\dfrac{28}{9}\right):\dfrac{-3}{7}=\dfrac{1}{6}:\dfrac{-3}{7}=-\dfrac{7}{18}\)
b)\(x=\left(\dfrac{7}{15}\cdot\dfrac{5}{3}\right)+\dfrac{3}{16}=\dfrac{7}{9}+\dfrac{3}{16}=\dfrac{139}{144}\)
c)\(x=\left(\dfrac{5}{6}-\dfrac{2}{5}\right).5=\dfrac{13}{6}\)
d)\(=>x\left(\dfrac{3}{4}-\dfrac{2}{5}\right)=\dfrac{1}{6}\cdot\left(\dfrac{3}{7}+\dfrac{5}{7}\right)\)
\(x\cdot\dfrac{7}{20}=\dfrac{4}{21}=>x=\dfrac{4}{21}\cdot\dfrac{20}{7}=\dfrac{80}{147}\)
a) \(2\dfrac{1}{2}\) - x + \(\dfrac{4}{5}\) = \(\dfrac{2}{3}\) - (\(-\dfrac{4}{7}\) )
b) \(-\dfrac{4}{7}\) - x = \(\dfrac{3}{5}\) - 2x
c) (\(\dfrac{3}{8}\) - \(\dfrac{1}{5}\) ) + (\(\dfrac{5}{8}\) - x) = \(\dfrac{1}{5}\)
\(a,2\dfrac{1}{2}-x+\dfrac{4}{5}=\dfrac{2}{3}-\left(-\dfrac{4}{7}\right)\\ \Rightarrow\dfrac{5}{2}-x+\dfrac{4}{5}=\dfrac{26}{21}\\ \Rightarrow\dfrac{5}{2}-x=\dfrac{46}{105}\\ \Rightarrow x=\dfrac{433}{210}\\ b,-\dfrac{4}{7}-x=\dfrac{3}{5}-2x\\ \Rightarrow2x-\dfrac{4}{7}-x=\dfrac{3}{5}\\ \Rightarrow2x-x=\dfrac{41}{35}\\ \Rightarrow x=\dfrac{41}{35}\\ c,\left(\dfrac{3}{8}-\dfrac{1}{5}\right)+\left(\dfrac{5}{8}-x\right)=\dfrac{1}{5}\\ \Rightarrow\dfrac{7}{40}+\dfrac{5}{8}-x=\dfrac{1}{5}\\ \Rightarrow\dfrac{4}{5}-x=\dfrac{1}{5}\\ \Rightarrow x=\dfrac{3}{5}.\)
Tìm x, biết:
a) \(\dfrac{1}{20}\) - (x - \(\dfrac{8}{5}\)) = \(\dfrac{1}{10}\)
b) \(\dfrac{7}{4}\) - (x + \(\dfrac{5}{3}\)) = \(\dfrac{-12}{5}\)
c) x - [\(\dfrac{17}{2}\) - \(\left(\dfrac{-3}{7}+\dfrac{5}{3}\right)\)] = \(\dfrac{-1}{3}\)
a) 1/20 - (x - 8/5) = 1/10
x - 8/5 = 1/20 - 1/10
x - 8/5 = -1/20
x = -1/20 + 8/5
x = 31/20
b) 7/4 - (x + 5/3) = -12/5
x + 5/3 = 7/4 + 12/5
x + 5/3 = 83/20
x = 83/20 - 5/3
x = 149/60
c) x - [17/2 - (-3/7 + 5/3)] = -1/3
x - (17/2 - 26/21) = -1/3
x - 305/42 = -1/3
x = -1/3 + 305/42
x = 97/14
a,\(\dfrac{2}{3}\)x\(\dfrac{5}{2}\):\(\dfrac{9}{5}\)
b,\(\dfrac{1}{3}\)x\(\dfrac{1}{4}\)+\(\dfrac{5}{6}\)
c,\(\dfrac{1}{2}\)-\(\dfrac{7}{8}\):\(\dfrac{7}{4}\)
d,\(\dfrac{6}{5}\)-\(\dfrac{4}{5}\)x\(\dfrac{3}{2}\)
Tìm x, biết:
a) \(\dfrac{3}{7}\)x - \(\dfrac{2}{3}\)x = \(\dfrac{10}{21}\)
b) \(\dfrac{7}{35}\) : (x - \(\dfrac{1}{3}\)) = \(-\dfrac{2}{25}\)
c) 3.(x - \(\dfrac{1}{2}\)) - 5. (x + \(\dfrac{3}{5}\)) = -x + \(\dfrac{1}{5}\)
a, \(\dfrac{3}{7}\)\(x\)- \(\dfrac{2}{3}\)\(x\) = \(\dfrac{10}{21}\)
(\(\dfrac{3}{7}\) - \(\dfrac{2}{3}\)) \(\times\) \(x\) = \(\dfrac{10}{21}\)
- \(\dfrac{5}{21}\) \(\times\) \(x\) = \(\dfrac{10}{21}\)
\(x\) = \(\dfrac{10}{21}\) : (-\(\dfrac{5}{21}\))
\(x\) = -2
b, \(\dfrac{7}{35}\) : (\(x-\dfrac{1}{3}\)) = - \(\dfrac{2}{25}\)
\(x\) - \(\dfrac{1}{3}\) = \(\dfrac{7}{35}\) : (- \(\dfrac{2}{25}\))
\(x\) - \(\dfrac{1}{3}\) = - \(\dfrac{5}{2}\)
\(x\) = - \(\dfrac{5}{2}\) + \(\dfrac{1}{3}\)
\(x\) = - \(\dfrac{13}{6}\)
c, 3.(\(x\) - \(\dfrac{1}{2}\)) - 5.(\(x\) + \(\dfrac{3}{5}\)) = - \(x\)+ \(\dfrac{1}{5}\)
3\(x\) - \(\dfrac{3}{2}\) - 5\(x\) - 3 = - \(x\) + \(\dfrac{1}{5}\)
- \(x\) + 5\(x\) - 3\(x\) = - \(\dfrac{3}{2}\) - 3 - \(\dfrac{1}{5}\)
\(x\) = - \(\dfrac{47}{10}\)
\(a,\dfrac{3}{7}x-\dfrac{2}{3}x=\dfrac{10}{21}\\ \Rightarrow x\left(\dfrac{3}{7}-\dfrac{2}{3}\right)=\dfrac{10}{21}\\ \Rightarrow x.-\dfrac{5}{21}=\dfrac{10}{21}\\ \Rightarrow x=-2\\ b,\dfrac{7}{35}:\left(x-\dfrac{1}{3}\right)=-\dfrac{2}{25}\\ \Rightarrow\dfrac{1}{5}:\left(x-\dfrac{1}{3}\right)=-\dfrac{2}{25}\\ \Rightarrow x-\dfrac{1}{3}=-\dfrac{5}{2}\\ \Rightarrow x=-\dfrac{13}{6}\\ c,3.\left(x-\dfrac{1}{2}\right)-5.\left(x+\dfrac{3}{5}\right)=-x+\dfrac{1}{5}\\ \Rightarrow3x-\dfrac{3}{2}-5x+5=-x+\dfrac{1}{5}\)
\(\Rightarrow x\left(3-5\right)-\dfrac{3}{2}+5=-x+\dfrac{1}{5}\\ \Rightarrow-2x-\dfrac{13}{2}=-x+\dfrac{1}{5}\\ \Rightarrow-x-\dfrac{13}{5}=\dfrac{1}{5}\\ \Rightarrow x=\dfrac{1}{5}-\dfrac{13}{5}\\ \Rightarrow x=-\dfrac{12}{5}.\)
a,73x−32x=2110⇒x(73−32)=2110⇒x.−215=2110⇒x=−2b,357:(x−31)=−252⇒51:(x−31)=−252⇒x−31=−25⇒x=−613c,3.(x−21)−5.(x+53)=−x+51⇒3x−23−5x+5=−x+51
Tìm x, biết:
a) \(\dfrac{-1}{10}\) + \(\dfrac{2}{5}\)x + \(\dfrac{7}{20}\) = \(\dfrac{1}{10}\)
b) \(\dfrac{1}{3}\) + \(\dfrac{1}{2}\) : x= \(-\dfrac{1}{5}\)
c) \(-\dfrac{2}{3}\) : x + \(\dfrac{5}{8}\) = \(-\dfrac{7}{12}\)
a, - \(\dfrac{1}{10}\) + \(\dfrac{2}{5}\)\(x\) + \(\dfrac{7}{20}\) = \(\dfrac{1}{10}\)
\(\dfrac{2}{5}\)\(x\) = \(\dfrac{1}{10}\) - \(\dfrac{7}{20}\) + \(\dfrac{1}{10}\)
\(\dfrac{2}{5}\) \(x\) = - \(\dfrac{3}{20}\)
\(x\) = - \(\dfrac{3}{20}\): \(\dfrac{2}{5}\)
\(x\) = - \(\dfrac{3}{8}\)
b, \(\dfrac{1}{3}\) + \(\dfrac{1}{2}\): \(x\) = - \(\dfrac{1}{5}\)
\(\dfrac{1}{2}\): \(x\) = - \(\dfrac{1}{5}\) - \(\dfrac{1}{3}\)
\(\dfrac{1}{2}\): \(x\) = - \(\dfrac{8}{15}\)
\(x\) = \(\dfrac{1}{2}\): (- \(\dfrac{8}{15}\))
\(x\) = - \(\dfrac{15}{16}\)
c, - \(\dfrac{2}{3}\): \(x\) + \(\dfrac{5}{8}\) = - \(\dfrac{7}{12}\)
\(\dfrac{2}{3}\): \(x\) = \(\dfrac{7}{12}\) + \(\dfrac{5}{8}\)
\(\dfrac{2}{3}\) : \(x\) = \(\dfrac{29}{24}\)
\(x\) = \(\dfrac{2}{3}\) : \(\dfrac{29}{24}\)
\(x\) = \(\dfrac{16}{29}\)
Tìm $x$, biết :
a) $-1,62+\dfrac{2}{5}+x=7$
b) $4 \dfrac{3}{5}-x=\dfrac{-1}{5}+\dfrac{1}{2}$
c) $\dfrac{-4}{7}-x=\dfrac{3}{5}-2 x$
d) $\dfrac{5}{7}-\dfrac{1}{13}+0,25=3 \dfrac{1}{2}-x$
a) x + \(\dfrac{2}{5}\) = \(\dfrac{1}{2}\)
b) x - \(\dfrac{2}{5}\) = \(\dfrac{2}{7}\)
c) \(\dfrac{3}{5}\) - x = \(\dfrac{1}{10}\)
d) x . \(\dfrac{3}{4}\) = \(\dfrac{9}{20}\)
e) x : \(\dfrac{1}{7}\) = 14
f) ( \(\dfrac{1}{4}\) + x ) . \(\dfrac{1}{2}\) = \(\dfrac{2}{5}\)
g) x . \(\dfrac{2}{3}\) - \(\dfrac{2}{3}\) = \(\dfrac{9}{12}\)
h) \(\dfrac{3}{4}\) + \(\dfrac{1}{4}\) : x = \(\dfrac{2}{5}\)
k) \(3\dfrac{4}{5}\) - x = \(\dfrac{18}{5}\)
l) x . \(2\dfrac{1}{3}\) = \(\dfrac{3}{4}\)
m) x . \(\dfrac{6}{11}\) + x . \(\dfrac{5}{11}\) = 2025
n) x . \(\dfrac{14}{9}\) - x . \(\dfrac{7}{9}\) + x . \(\dfrac{5}{9}\) = 2
Các bạn làm theo cách bình thường ở lớp 5 cho mính nhé!
Chú ý: dấu "." là dấu nhân.
a: x+2/5=1/2
=>x=1/2-2/5=5/10-4/10=1/10
b; x-2/5=2/7
=>x=2/7+2/5=10/35+14/35=24/35
c: 3/5-x=1/10
=>x=3/5-1/10=6/10-1/10=5/10=1/2
d: x*3/4=9/20
=>x=9/20:3/4=9/20*4/3=36/60=3/5
e: x:1/7=14
=>x=14*1/7=2
f: =>x+1/4=2/5:1/2=4/5
=>x=4/5-1/4=16/20-5/20=11/20
g: =>x*2/3=9/12+2/3=3/4+2/3=9/12+8/12=17/12
=>x=17/12:2/3=17/12*3/2=51/24=17/8
Tìm x:
\(\dfrac{3}{5}\) : x = \(\dfrac{1}{3}+\dfrac{1}{2}\) x : \(\dfrac{7}{12}\) = 2 x - \(\dfrac{3}{2}\) = \(\dfrac{11}{4}-\dfrac{5}{4}\) x + \(\dfrac{5}{4}\) = \(\dfrac{3}{2}+\dfrac{7}{12}\)
`3/5 : x =1/3 +1/2`
` 3/5 : x= 2/6 +3/6`
` 3/5 : x= 5/6`
` x= 3/5 : 5/6`
` x= 3/5 xx 6/5`
` x= 18/25`
__
`x: 7/15 =2`
` x= 2xx 7/15`
` x= 14/15`
__
`x-3/2=11/4-5/4`
`x-3/2= 6/4`
`x= 3/2 +3/2`
`x= 6/2`
`x=3`
__
`x+5/4 = 3/2+7/12`
`x+5/4 = 18/12+7/12`
`x+5/4 = 25/12`
`x= 25/12-5/4`
`x= 25/12- 15/12`
`x= 10/12`
`x= 5/6`